The energy transition underway in the world and in Latin America - Rodrigues, Manoel Gonçalves (2024)
After the oil shocks of the 1970s, the need to find substitutes for oil and its derivatives began to gain momentum. Efforts initiated to replace oil and its derivatives with alternatives, aiming to build an energy matrix less dependent on fossil fuels with innovative technologies. In response, Brazil—the largest and most industrialized country in Latin America—focused on bioenergy. Solidify this strategy later with the development of ethanol and biofuels. Additionally, Brazil incorporated alternative sources such as solar and wind energy, alongside its pre-existing hydroelectric base. Collectively, these efforts intended to drive the global and Latin American energy transition from fossil fuels to renewable energy sources. However, by the mid-2010s, South America’s energy supply continued to rely heavily on fossil fuels, particularly oil and natural gas